2004
DOI: 10.1074/jbc.m401522200
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Intracellular Processing of the Endogenous Cystic Fibrosis Transmembrane Conductance Regulator in Epithelial Cell Lines

Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR) is a cAMP-dependent protein kinase A-activated chloride channel that resides on the apical surface of epithelial cells. One unusual feature of this protein is that during biogenesis, ϳ75% of wild type CFTR is degraded by the endoplasmic reticulum (ER)-associated degradative (ERAD) pathway. Examining the biogenesis and structural instability of the molecule has been technically challenging due to the limited amount of CFTR expressed in epithelia. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
117
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(137 citation statements)
references
References 65 publications
(74 reference statements)
14
117
1
2
Order By: Relevance
“…epithelial cells in which endogenous CFTR is studied have less band B protein than that detected when recombinant CFTR is expressed (31,32). Treatment with the miR-138 mimic and the SIN3A DsiRNA increased cAMP-stimulated G t (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…epithelial cells in which endogenous CFTR is studied have less band B protein than that detected when recombinant CFTR is expressed (31,32). Treatment with the miR-138 mimic and the SIN3A DsiRNA increased cAMP-stimulated G t (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…A recent study has shown that inefficient processing of CFTR occurs only in heterologous overexpression systems. In epithelial cells, endogenously expressed CFTR is efficiently processed and exported to postGolgi compartments (Varga et al, 2004).…”
Section: An Outcome Of Overloading Of the Endoplasmic Reticulum (Er) mentioning
confidence: 99%
“…This is particularly relevant to F508 CFTR as over accumulation of this mutant protein in the ER induces such a response, leading to downregulation of CFTR endogenous transcription (Rab et al, 2007;Bartoszewski et al, 2008). Aside from the above two, the inherent variation in the cellular chaperone machinery among different tissues or cell types will also significantly affect the cell surface functional expression of F508 CFTR (Varga et al, 2004;X. Wang et al, 2008;Rowe et al, 2010).…”
Section: Chaperone Environment: a Critical But Complex Part Of The Eqmentioning
confidence: 99%